2012
DOI: 10.1212/wnl.0b013e318249f6a9
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell omega-3 fatty acid levels and markers of accelerated brain aging

Abstract: Objective: Higher dietary intake and circulating levels of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have been related to a reduced risk for dementia, but the pathways underlying this association remain unclear. We examined the cross-sectional relation of red blood cell (RBC) fatty acid levels to subclinical imaging and cognitive markers of dementia risk in a middleaged to elderly community-based cohort. Methods:We related RBC DHA and EPA levels in dementia-free Framingham Study participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
165
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 41 publications
16
165
2
5
Order By: Relevance
“…PNPLA3 (I148M) GG was associated with decreased DHA enrichment but was not associated with EPA enrichment. It is known that omega-3 fatty acids are rapidly incorporated into plasma membranes where they affect membrane fluidity and membrane permeability (36) and that measurement of erythrocyte DHA and EPA enrichment is considered a good proxy for omega-3 fatty acid enrichment and bioavailability in liver (37). However, based on our results, PNPLA3 I148M is involved in DHA/EPA mobilization in liver and subjects with PNPLA3 (I148M) GG genotype have lower levels of DHA (38).…”
Section: Discussionmentioning
confidence: 56%
“…PNPLA3 (I148M) GG was associated with decreased DHA enrichment but was not associated with EPA enrichment. It is known that omega-3 fatty acids are rapidly incorporated into plasma membranes where they affect membrane fluidity and membrane permeability (36) and that measurement of erythrocyte DHA and EPA enrichment is considered a good proxy for omega-3 fatty acid enrichment and bioavailability in liver (37). However, based on our results, PNPLA3 I148M is involved in DHA/EPA mobilization in liver and subjects with PNPLA3 (I148M) GG genotype have lower levels of DHA (38).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, in the Framingham Offspring cohort (n 5 1,575, 54% women, average age 67 years), participants with an omega-3 index in the first quartile had a smaller average brain volume (20.49%) compared with those in the upper 3 quartiles, which was described as being equivalent to approximately 2 years of normal brain aging. 13 In our multicenter, women-only study, we found no relations between ischemic lesion volumes (which represented both diffuse small-vessel disease and the hyperintensities that surround focal lesions) and marine omega-3 FAs. This is in contrast to the Framingham study, which reported greater white matter hyperintensity volumes as a percentage of intracranial volume with lower DHA levels.…”
mentioning
confidence: 52%
“…This is in contrast to the Framingham study, which reported greater white matter hyperintensity volumes as a percentage of intracranial volume with lower DHA levels. 13 A plasma nutrient biomarker pattern that included EPA, DHA, and 12 other nutrients was also inversely related to white matter hyperintensity volumes. e1 The Cardiovascular Health Study (n 5 2,465, 59% women, average age 75 years) reported less likelihood of subclinical infarcts, defined as ischemic lesions $3 mm in diameter, for participants who ate fatty, nonfried fish more frequently.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…AD and MCI patients exhibit lower levels of long-chain polyunsaturated fatty acids (PUFA) of Omega-3 series in RBC membranes compared with healthy controls [77]. Moreover, lower erythrocytes levels of Omega-3 PUFA, eicosapentaenoic acid and docosahexaenoic acid, were shown to be associated with smaller brain volumes and a 'vascular' pattern of cognitive impairment [78]. The findings in AD erythrocytes support the erythrocytic/vascular hypothesis of AD and contribute to a molecular signature of AD in RBCs.…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 99%